Optimization design and drag reduction characteristics of bionic borehole heat exchanger - Zhang, Jiansong; Liu, Yongsheng; Qin, Xing; Dou, Zijun; Meng, Qingsheng; Xu, Xiaonan; Lv, Jianguo (Frontiers in Energy Research, 2022)
As a renewable energy source, geothermal energy has drawn attention because it is clean, low-carbon, resource-rich, stable, and sustainable supply. In the mining and operation of a geothermal energy system, there is a certain amount of fluid resistance in the borehole heat exchanger where the fluid flows. As the resistance in the conventional borehole heat exchanger(CBHE) accumulates with the length increase, the pumping power increases, resulting in energy loss and affecting the operation of the entire geothermal system. A bionic borehole heat exchanger (BBHE) is designed by using a circular groove as a bionic unit on the basis of the bionic non-smooth surface hypothesis. The circular groove's depth, width, and slot pitch are its structural characteristics. Where the fluid faces the least resistance, minimization of the pressure drop was the optimization goal. Based on the outcomes of a CFD numerical simulation and genetic algorithm optimization study. These are the BBHE's ideal structural parameters: diameter is 60 mm, 66 mm for the groove width, 418 mm for the slot pitch, and 80 mm for the groove depth. Compared to the CBHE, under identical numerical simulation settings, the fluid resistance reduction rate of BBHE can reach 13 %. Increasing fluid velocity in the BBHE can increase the temperature transmission rate. The study's findings can serve as a reliable source of scientific information for the use and management of geothermal energy.